2010
DOI: 10.3171/2009.12.focus09281
|View full text |Cite
|
Sign up to set email alerts
|

Correction of lumbar coronal plane deformity using unilateral cage placement

Abstract: The authors describe a surgical technique for the correction of symptomatic degenerative lumbar scoliosis. Using a single, unilateral, interbody cage placed on the concave side of the coronal deformity, combined with a dorsal decompression and instrumented posterolateral fusion, this technique has resulted in excellent curve correction, fusion results, and clinical outcomes in a series of 4 patients. Each of these patients presented with intractable, axial low-back pain and symptomatic unilateral nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Meanwhile, there is a necessity to identify which implant factor most impacts restoration of asymmetric intervertebral space. Due to effect of the off-center placement of the cage on the coronal curve correction noted in previous study (36), we analyzed the horizontal position of the cage in the univariable linear regression analysis but found no significant effect on ΔIHD, suggesting that the proximity to midline of the cage had no significant effect on the correction of asymmetric intervertebral space. However, multivariable linear regression and mediation analyses revealed that preoperative DWA and the angle of the lower pedicle screw exerted positive direct and indirect effects on ΔIHD.…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, there is a necessity to identify which implant factor most impacts restoration of asymmetric intervertebral space. Due to effect of the off-center placement of the cage on the coronal curve correction noted in previous study (36), we analyzed the horizontal position of the cage in the univariable linear regression analysis but found no significant effect on ΔIHD, suggesting that the proximity to midline of the cage had no significant effect on the correction of asymmetric intervertebral space. However, multivariable linear regression and mediation analyses revealed that preoperative DWA and the angle of the lower pedicle screw exerted positive direct and indirect effects on ΔIHD.…”
Section: Discussionmentioning
confidence: 95%
“…First, the posterior elements that include the spinous process, bilateral lamina, and the adjacent facet joints were completely removed. This degree of bone resection allows for the involved nerve roots to be completely decompressed in addition to a dorsal release of the coronal deformity and passive deformity correction [26]. When compared to the TLIF and PLIF, PCO could effectively prevent the nerve root injury on the convex side of the lumbosacral curve in the procedure of pedicle screw-rod compression.…”
Section: Discussionmentioning
confidence: 99%
“…The most possible explanation may be that, posterior distraction of the lumbosacral concavity through pedicle screw-rod provides direct disc height restoration and scoliosis correction, but may decrease the lordosis inevitably, since it is a kyphosing technique. By using a lordotic rod, the negative impact of the compression on the concave side would be minimized [26].…”
Section: Discussionmentioning
confidence: 99%
“…An excellent mean correction of 31.7° and 44.8° in the coronal and sagittal planes, respectively, was achieved. Thus, the use of TLIF for deformity surgery, as described by Heary and Karimi, 8 appears to afford the opportunity for improved deformity correction.…”
Section: Discussionmentioning
confidence: 99%